Ultrasound-Guided Percutaneous Core Needle Biopsy of Peripheral Pulmonary Nodules ≤ 2 cm: Diagnostic Performance, Safety and Influence Factors - Huang, Weijun; Ye, Jieyi; Qiu, Yide; Peng, Weiwei; Lan, Ninghui; Huang, Ting; Ou, Yinghui; Deng, Xiaoyun; Li, Yingjia (Frontiers in Oncology, 2021)
Purpose To evaluate diagnostic performance and safety of ultrasound-guided needle biopsy in the diagnosis of peripheral pulmonary nodules (PPLs) ≤ 2 cm, and the influence factors of sample adequacy and safety. Materials and Methods 194 patients (99 men, 95 women; mean age, 56.2 ± 13.7 years) who received biopsy for PPLs ≤ 2 cm between January 2014 to January 2019 were included. Variables including patient demographics, lesion location, lesion size, presence of lesion necrosis, presence of emphysema on CT, patient position, biopsy needle size and number of needle passes were recorded. Univariate analysis and multivariate logistic regression analysis were performed to explore the influence factor of sample adequacy and safety. Results Biopsy specimens were adequate for diagnosis in 161/194 (83%) cases; the diagnostic accuracy was 81.4% (158/194). The overall complication rate was 8.8% (17/194), including pneumothorax, hemoptysis and pleural effusion, which occurred in 2.1% (4/194), 5.2% (10/194), and 1.5% (3/194) of patients, respectively. The incidence of pneumothorax in the 16-gauge-needle group were significantly higher than that of the 18-gauge-needle group (5.6% vs 0%, P=0.018). Adequate sampling of 16-gauge and 18-gauge needles were achieved in 90.3%(65/72) and 78.7%(96/122) cases, respectively. Multivariate logistic regression analysis revealed needle size (16-gauge vs 18-gauge) was an independent influence factors of sample adequacy (P=0.015, odds ratio=3.419). A receiver operating characteristic curve was plotted and the area under the curve was 0.774. Conclusion US-guided percutaneous needle biopsy is a feasible and safe technique for small PPLs ≤ 2 cm. Needle size is an independent influence factor of sample adequacy and post-procedure pneumothorax. Sixteen-gauge needle has the advantage of achieving adequate sample for pathological analysis, though the risk of pneumothorax should be alerted.